The concept of the truth when the fundamentalists - Alaa Abdul Hussein Radhi (Journal of College of Education, 2024)
This research is concerned with studying the truth from the point of view of the fundamentalists, Because the truth is of great importance on which many fundamentalists investigations are based. And belief according to the diversity of the word and its hesitation between the real and metaphorical meaning. This study came as follows: An introduction on the importance of the subject, the reasons for choosing it, And its organizational structure. The third section clarifies the issues that characterize the truth, The issue of turning the metaphor into reality, And the fundamentalists opinions regarding the establishment and denial of the legal truth, And finally the conclusion comes, Which carries with it some visions and conclusions .